A Novel Method for Constructing the S-Box Based on Spatiotemporal Chaotic Dynamics - Liu, Liyan; Zhang, Yingqian; Wang, Xingyuan (Applied sciences, 2018)
A novel construction method for a random S-box by using the spatiotemporal nonlinear chaotic system is proposed. The chaotic sequences of the spatiotemporal chaotic system are applied to construct an initial S-box. Then, the permutation operation between independent chaotic sequences is performed to shuffle the elements of the S-box randomly. In comparisons with the former schemes, the results of the performance analysis indicate that the obtained S-box has a better output bit independence criterion and a stronger ability to resist linear password attacks. It also has a high dimensional feature due to the spatiotemporal chaotic dynamical behaviors. The proposed scheme holds superior cryptographic features.